Bond market opening, monetary policy, and systemic financial risks – An empirical study based on the TVP-SV-VAR model - Wei-Ying Ping; Yu-Wen Hu; Liang-Qing Luo (PLoS ONE, 2025)
While the opening of the bond market provides strong support for high-level financial opening, it also accelerates the accumulation of systemic financial risks, thereby affecting the high-quality development of China’s finance. Based on data from 2003 to 2024, this paper measures China’s bond market opening, monetary policy, and systemic financial risks, and employs a TVP-SV-VAR model to investigate the time-varying relationships among bond market opening, monetary policy, and systemic financial risks. The findings are as follows: (1) The impact of bond market opening on China’s systemic financial risks exhibits time-varying characteristics; (2) Contractionary monetary policy helps curb systemic financial risks, but this effect marginally diminishes when facing external structural shocks; (3) The improvement of interest rate transmission mechanisms and the transition toward price-based monetary policy can significantly enhance the sustainability of monetary policy’s regulatory role in systemic financial risks; (4) There exists a significant linkage effect between bond market opening and monetary policy, but this effect is subject to time-varying influences from the progress of domestic institutional reforms and cross-border capital anomalies.